BANKS CLAIMS ON PRIVATE SECTOR AND MONETARY POLICY CHANNEL - Suhartono Suhartono; Abdul Mongid; FX Soegeng Notodihardjo (Jurnal Keuangan dan Perbankan, 2010)
Banking industry is the main channel of monetary policy. As emphasized by the information-theoreticapproach, a central function of banks was to screen and monitor borrowers, thereby overcoming informationand incentive problems. By developing expertise in gathering relevant information, as well as by maintainingongoing relationships with customers, banks could control their business. Since 2000, Bank Indonesiastarted to implement a new framework of monetary policy and was initially applied in July 2005. Theimpact of new monetary policy framework was investigated within the banking capital adequacy regulationand economics framework. We found that stock exchange index (IHSG) was positive and significant at1%. Other variables such as FINSHARE, GM2, NPL, CAR, BIRATE were negative and significant. In general,we concluded that banking sector claims on the private sector was one of important monetary policychannels.